2018
DOI: 10.1002/mp.12858
|View full text |Cite
|
Sign up to set email alerts
|

Positioning accuracy and daily dose assessment for prostate cancer treatment using in‐room CT image guidance at a proton therapy facility

Abstract: The correction of repositioning along the AP and SI direction from conventional bone matching in CT image-guided proton therapy was found to be effective to maintain the dose constraint of the rectum and the dose coverage of the prostate. This work indicated that prostate cancer treatment by prostate matching using CT image guidance may be effective to reduce the rectal complications and achieve better tumor control of the prostate. However, an adaptive approach is desirable to maintain better dose coverage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 28 publications
1
56
0
Order By: Relevance
“…The treatment planning created initially based on above conditions was used through entire treatment with our CT image guidance. More detailed information was described in our report …”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…The treatment planning created initially based on above conditions was used through entire treatment with our CT image guidance. More detailed information was described in our report …”
Section: Methodsmentioning
confidence: 95%
“…In this study, we analyzed the interfractional variation in the prostate, rectum, and SVs utilizing almost full sets of in‐room CT images acquired throughout prostate cancer treatment at a proton therapy facility . We directly measured the movements of the different portions of each anatomical structure along the relevant coordinate axes for proton therapy with opposed lateral beams.…”
Section: Introductionmentioning
confidence: 99%
“…27 When comparing image guidance on BA versus guidance on the prostate-rectal wall, Maeda et al found superior or comparable target coverage for the latter. 28 In their study, the passive scattering technique was, however, planned to compensate for prostate motion of AE10 mm in relation to the BA, which was more than the recorded differences between the 2 setup techniques in their patient material. In our training material, such large motion was rare (2.5%) and nonexistent among the testing patients Pat.20 Pat.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses have employed varying strategies to accumulate fractional doses for prostate cancer radiotherapy on the basis of widely available but low-quality CBCT imaging, including enhanced or iterative CBCT approaches, portal dose measurements or rigid registration strategies, albeit with limitations regarding dose mapping ( 12 , 15 , 31 , 32 ). Dosimetric analyses based on daily diagnostic CT imaging have only been reported for proton radiotherapy, as in-room CT scanners are more widely available at the respective facilities, given the necessity for high-resolution imaging to compensate for higher proton range uncertainties due to anatomic alterations ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%